EzPlanAbility / Muhammad Faris Fazrin Ibrahim … [et al.] - Ibrahim, Muhammad Faris Fazrin; Asli, Muhammad Nazamudin; Sudiroo, Nurul Fatihah; Rashid Vincent Abdullah, Nurfatin Nabilah; Nasib, Nur Ezzaty; Azis, Siti Nur Sakinah; Hashim, Nurhaslinda (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
EzPlanAbility application is an app that was designed to help parents plan their disabled children's long-term financial future. Raising a child with disabilities is very challenging, especially when it comes to planning and managing their financial security. EzPlanAbility will collect the personal information of users and their children and provide financial aid information. After that, the user can also raise awareness of financial planning for children with disabilities. This app has been creating a secure and fulfilling future for their entire family. Every single day, the users have to face a multitude of uncertainties regarding their disabled child's future needs. For example, medical care, specialized equipment, and potential limitations on earning capacity all contribute to a complex financial landscape. Unfortunately, many parents lack the resources or knowledge necessary to develop a sound financial plan that ensures their child's well-being throughout their life. This app will guide parents through a personalized needs assessment, considering many factors, such as the child's disability, current and future care requirements, and potential government benefits. EzPlanAbility also helps users create and monitor a personalized budget, allowing them to track expenses related to healthcare, therapies, and other disability-related costs. This fosters informed decision-making and helps ensure funds are allocated effectively. In addition, the application simplifies bureaucratic processes and streamlines financial management through features such as digital OKU card registration and reminders about government benefits. By leveraging technology and user-friendly tools, EzPlanAbility empowers users to navigate the complexities of financial planning and build a brighter future for their children.